2015
DOI: 10.1371/journal.pmed.1001924
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Benefits of Nalmefene in the Treatment of Adult Alcohol Dependence: A Systematic Literature Review and Meta-Analysis of Published and Unpublished Double-Blind Randomized Controlled Trials

Abstract: BackgroundNalmefene is a recent option in alcohol dependence treatment. Its approval was controversial. We conducted a systematic review and meta-analysis of the aggregated data (registered as PROSPERO 2014:CRD42014014853) to compare the harm/benefit of nalmefene versus placebo or active comparator in this indication.Methods and FindingsThree reviewers searched for published and unpublished studies in Medline, the Cochrane Library, Embase, ClinicalTrials.gov, Current Controlled Trials, and bibliographies and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 34 publications
(33 reference statements)
0
61
0
2
Order By: Relevance
“…In the alcohol research literature, for example, Shaham and De Wit (2016) noted that other drugs that were effective in animal models of stress-induced reinstatement (e.g., alpha-2 adrenoceptor agonists such as clonidine and lofexidine) translated to showing efficacy against stress-induced drug craving in human laboratory studies (Mantsch et al 2016; Sinha et al 2011). Similarly, acamprosate and the opioid receptor antagonists naltrexone and nalmefene reduce operant oral ethanol self-administration in rats under a variety of conditions (Rassnick et al 1992; Heyser et al 1998; Heyser et al 2003; Sabino et al 2006; Ji et al 2008; Gilpin et al 2008; Walker and Koob 2008) and, analogously, show some efficacy to mitigate alcohol use disorders (see Stevenson et al 2015; Keating 2013; Rösner et al 2010; Plosker 2015; but see Palpacuer et al 2015). Gabapentin reduced both the anxiogenic-like behavior and the increased ethanol self-administration observed in withdrawn, ethanol dependent rats, but not non-dependent rats (Roberto et al 2008; Besheer et al 2016; Watson et al 1997) and was found to improve emotional function and reduce insomnia and alcohol use in abstinent alcoholics (Bonnet et al 2007; Malcolm et al 2007; Brower et al 2008; Myrick et al 2009; Mason et al 2014).…”
Section: Performance In Animal Modelsmentioning
confidence: 99%
“…In the alcohol research literature, for example, Shaham and De Wit (2016) noted that other drugs that were effective in animal models of stress-induced reinstatement (e.g., alpha-2 adrenoceptor agonists such as clonidine and lofexidine) translated to showing efficacy against stress-induced drug craving in human laboratory studies (Mantsch et al 2016; Sinha et al 2011). Similarly, acamprosate and the opioid receptor antagonists naltrexone and nalmefene reduce operant oral ethanol self-administration in rats under a variety of conditions (Rassnick et al 1992; Heyser et al 1998; Heyser et al 2003; Sabino et al 2006; Ji et al 2008; Gilpin et al 2008; Walker and Koob 2008) and, analogously, show some efficacy to mitigate alcohol use disorders (see Stevenson et al 2015; Keating 2013; Rösner et al 2010; Plosker 2015; but see Palpacuer et al 2015). Gabapentin reduced both the anxiogenic-like behavior and the increased ethanol self-administration observed in withdrawn, ethanol dependent rats, but not non-dependent rats (Roberto et al 2008; Besheer et al 2016; Watson et al 1997) and was found to improve emotional function and reduce insomnia and alcohol use in abstinent alcoholics (Bonnet et al 2007; Malcolm et al 2007; Brower et al 2008; Myrick et al 2009; Mason et al 2014).…”
Section: Performance In Animal Modelsmentioning
confidence: 99%
“…Two studies showed a significant benefit in both primary endpoints [88,89], one study in the reduction of heavy drinking days but not in total alcohol consumption [90], and the other 1-year safety study that was not significant at the predefined endpoint [91]. Several meta-analyses on the ITT analyses are available now, but many were not based on the specific population defined by the EMA approved indication (“targeted use in high-risk level drinking alcohol-dependent patients”), see [92,93], and only the most recent takes the EMA-approved indication of nalmefene into account [87]. Here the average effect size for “the EMA indication” was 0.33, for the ITT population it was 0.20 [87].…”
Section: Review Of Pharmacotherapy Trials Prospectively Testing An Exmentioning
confidence: 99%
“…The rate of discontinuation due to adverse events was higher in the groups receiving nalmefene than in the placebo group (18.1%, 18.5%, and 4.5%, respectively, for nalmefene 20‐mg, nalmefene 10‐mg, and placebo). These characteristics were already observed in a meta‐analysis of the initial trials submitted to the European Medicine Agency …”
mentioning
confidence: 53%
“…No RCT has assessed the efficacy of nalmefene in the long term. Only one RCT has assessed the efficacy of nalmefene after 1 year of treatment, and showed limited and inconsistent efficacy on consumption outcomes . Currently, the harm‐reduction approach is based on models that are basically an extrapolation of the results from subgroup analyses of the previous pivotal RCT beyond the trial time horizon .…”
mentioning
confidence: 99%